1966
DOI: 10.1007/bf00022320
|View full text |Cite
|
Sign up to set email alerts
|

A study of diallel crosses between varieties of nicotiana tabacum L. for yield components

Abstract: To predict the behaviour of selections in the F 1 generation itself before taking them to the advanced generations for further screening, the applicability of diallel cross analysis was studied .For this purpose four N. tabacum varieties were crossed in all combinations to constitute a diallel system and data collected on green leaf, saleable leaf i .e . sum of bright leaf and medium leaf yields, number of days taken for flowering, length and breadth of the middle leaves at maturity of the F l plants were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Some previous investigations of the inheritance of major tobacco traits (yield, plant height, leaf number, days to flowering, leaf length and width) using graphic analysis show contradictory results. Starting from yield, a major tobacco trait, according to the studies made so far overdominant inheritance was estimated by graphic analysis (Jung et al 1982, Šmalcelj 1983, Butorac et al 1999), but partial dominance was also found (Gopinath et al 1966, Shamsuddin et al 1980, Pandeya et al 1983). In our present investigations, according to the graphic analysis, yield was inherited overdominantly in both years of investigation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some previous investigations of the inheritance of major tobacco traits (yield, plant height, leaf number, days to flowering, leaf length and width) using graphic analysis show contradictory results. Starting from yield, a major tobacco trait, according to the studies made so far overdominant inheritance was estimated by graphic analysis (Jung et al 1982, Šmalcelj 1983, Butorac et al 1999), but partial dominance was also found (Gopinath et al 1966, Shamsuddin et al 1980, Pandeya et al 1983). In our present investigations, according to the graphic analysis, yield was inherited overdominantly in both years of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Different results were obtained depending on the investigated traits, and also on the genetic materials as well as the leaf position on the stalk. In most studies additive variance in the inheritance of leaf width was estimated (Gopinath et al 1966, Espino and Gil 1980, Ibrahim and Avravtovscukova 1982. According to our results, leaf width was inherited overdominantly in one year and partly dominantly in the other year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations